Identification of spliceosome components pivotal to breast cancer survival. Issue 6 (3rd June 2021) - An, Jing; Luo, Zhehui; An, Weiwei; Cao, Difei; Ma, Jianli; Liu, Zhaoliang
ABSTRACT: Cancer cells employ alternative splicing (AS) to acquire splicing isoforms favouring their survival. However, the causes of aberrant AS in breast cancer are poorly understood. In this study, the METABRIC (Molecular Taxonomy of Breast Cancer International Consortium) data were analysed with univariate feature selection. Of 122 analysed spliceosome components, U2SURP, PUF60, DDX41, HNRNPAB, EIF4A3, and PPIL3 were significantly associated with breast cancer survival. The top 4 four genes, U2SURP, PUF60, DDX41, and HNRNPAB, were chosen for further analyses. Their expression was significantly associated with cancer molecular subtype, tumour stage, tumour grade, overall survival (OS), and cancer-specific survival in the METABRIC data. These results were verifiable using other cohorts. The Cancer Genome Atlas data unveiled the elevated expression of PUF60, DDX41, and HNRNPAB in tumours compared with the normal tissue and confirmed the differential expression of the four genes among cancer molecular subtypes, as well as the associations of U2SURP, PUF60, and DDX41 expression with tumour stage. A meta-analysis data verified the associations of U2SURP, PUF60, and HNRNPAB expression with tumour grade, the associations of PUF60, DDX41, and HNRNPAB expression with OS and distant metastasis-free survival, and the associations of U2SURP and HNRNPAB expression with relapse-free survival. Experimentally, we demonstrated that inhibiting the expression of the four genes separately suppressed cell colony formation and slowed down cell growth considerably in breast cancer cells, but not in immortal breast epithelial cells. In conclusion, we have identified U2SURP, PUF60, DDX41, and HNRNPAB are spliceosome-related genes pivotal for breast cancer survival.